The Bronx in Australia: The Metaphoric Stigmatization of Public Housing Tenants in Australian Towns and Cities - Birdsall-Jones, Christina (Sage Publications, 2013)
This paper contributes to the literature on the stigmatization of Australian public housing tenants and to the literature on Australian housing metaphors, explaining the usage of “the Bronx” as a means of stigmatizing country town and suburban localities dominated by public housing. It compares four Australian situations where the marginalization of the poor is expressed through the typification of the area in which they live as “the Bronx” by local usage, the media or both, comparing these with a fifth situation that matched the signal characteristics of this typification but escaped being so labeled. An examination of the Bronx’s (New York City) history shows the development of its reputation as a metaphor for the urban ghetto. The results of qualitative fieldwork undertaken in the Western Australian towns of Kalgoorlie, Carnarvon, and Broome are compared with media representations of analogous stigmatizations in New South Wales.